Solubility Enhancement of Budesonide and Statistical Optimization of Coating Variables for Targeted Drug Delivery. (10th April 2014) - Bhatt, Himanshu; Naik, Bhargavi; Dharamsi, Abhay
Abstract : The purpose of the research was to present Budesonide (BUD) as a novel formulation showing improved aqueous solubility, which may decrease variability inC max ⁡ andT max ⁡ found in inflammatory bowel disease (IBD) patients, and drug targeting to colon. To improve aqueous solubility, solid dispersion (SD) of the BUD with poloxamer 188 was prepared by melting method. Physical characterization of solid dispersion was performed. The SD was used to prepare tablet equivalent to 9 mg of BUD. The tablet was coated with enteric polymers Eudragit S100 and Eudragit L100 to target colon. The ratio of polymers and percentage coating was optimized using statistical design. Variables studied in design were ratio of enteric polymers and the effect of percentage coating on in vitro drug release. Dissolution at different pH showed that drug release in colon could be modified by optimizing the ratio of polymers and percentage coating. The dissolution data showed that the percentage coating and ratio of polymers are very important to get lag time and optimum formulation. The optimized batch from statistical design was kept under accelerated condition for three months. After accelerated stability study, there was no significant change in the drug release.